Study of prevalence of diabetes, hypertension, hypercholesterolaema and obesity in non academic staff of a Medical Faculty (DHHO study) using a screening program - de Abrew, W K; Weeraratne, C L; Wijeratne, T D; Perera, H; de Abrew, A G; Lakshmee, D L S (University of Colombo, 2010)
Prevalence of non communicable diseases (NCDs) in state sector employees of Sri Lanka is largely unknown hindering the implementation of preventive and control measures.